2020
DOI: 10.1021/acs.biomac.0c00903
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Self-Assembly Using Tannic Acid and Phenylboronic Acid-Modified Copolymers for Potential Protein Delivery

Abstract: Tannic acid (TA) can form stable complexes with proteins, attracting significant attention as protein delivery systems. However, its systemic application has been limited due to nonspecific interaction. Here, we report a simple technique to prepare systemically applicable protein delivery systems using sequential self-assembly of a protein, TA, and phenylboronic acid-conjugated PEG-poly(amino acid) block copolymers in aqueous solution. Mixing the protein and TA in aqueous solution led to covering of the protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 34 publications
2
28
0
Order By: Relevance
“…17 In addition, our previous study revealed that a 50% introduction of FPBA maintained water solubility of the polymer and permitted the formation of boronate esters multivalently with the galloyl groups of TA, resulting in the formation of the β-Gal/TA/PEG-P[Lys/Lys(FPBA)] ternary complexes. 13 In the present study, PEG-P[Lys/Lys(FPBA)] was added to the β-Gal/TA complex in aqueous solution, and the complex formation was confirmed by electrophoresis (Figure 2a). Compared with β-Gal alone, β-Gal/TA exhibited a longer migration distance toward the anode due to the anionic property of TA, while the β-Gal ternary complex migrated to the cathode, indicating the interaction of the cationic PEG-P[Lys/Lys(FPBA)] with β-Gal/TA.…”
Section: ■ Results and Discussionsupporting
confidence: 50%
See 4 more Smart Citations
“…17 In addition, our previous study revealed that a 50% introduction of FPBA maintained water solubility of the polymer and permitted the formation of boronate esters multivalently with the galloyl groups of TA, resulting in the formation of the β-Gal/TA/PEG-P[Lys/Lys(FPBA)] ternary complexes. 13 In the present study, PEG-P[Lys/Lys(FPBA)] was added to the β-Gal/TA complex in aqueous solution, and the complex formation was confirmed by electrophoresis (Figure 2a). Compared with β-Gal alone, β-Gal/TA exhibited a longer migration distance toward the anode due to the anionic property of TA, while the β-Gal ternary complex migrated to the cathode, indicating the interaction of the cationic PEG-P[Lys/Lys(FPBA)] with β-Gal/TA.…”
Section: ■ Results and Discussionsupporting
confidence: 50%
“…The cellular uptake of β-Gal/TA was ∼80% lower than that of free β-Gal, because serum components in the medium may interact with β-Gal/TA, compromising interaction with the cell membrane as previously reported. 13 The ternary complex also exhibited a cellular uptake lower than that of free β-Gal, but it was higher than that of β-Gal/TA. The PEG shell of the ternary complex might inhibit the aforementioned nonspecific interaction of TA, which might lead to the moderate cellular uptake.…”
Section: ■ Results and Discussionmentioning
confidence: 95%
See 3 more Smart Citations